An exploratory study of social selling on LinkedIn: The concept and its implications - Bilro, R. G.; Loureiro, S. M. C. (Marketing and Smart Technologies. Smart Innovation, Systems and Technologies, 2020)
Due to the digital transformation, the purchasing process is evolving, rising the need to reinvent the sales process. Through marketing and sales tools and tactics, social selling presents itself as a strategy that supports the company to position itself at the beginning of consumers journey. It also allows firms to retake its influence in the decisionmaking process, through the education of customers, building and strengthening relationships based on trust, customized customers strategies and generation of value and content. Through a qualitative methodology using in-depth interviews, this research aims to shed light on a topic that is still under-explored and to propose the application of this strategy in firms. From this study, both theoretical and managerial implications are offered.